Stroke in young and old patients: a retrospective study - Valente, João (1996)
Material and methods: We performed a retrospective review of medical records of patients with a diagnosis of CVD between February 1989 and December 1993 at Internal Medicine Ward of a Hospital Center in area of Oporto. We analysed: age and sex; types of CVD and temporal profile; VRF (previous AVC, hypertension (HT), diabetes, dyslipidemia, heart disease, cigarette smoking and alcohol consumption); morbility and morta lity; blood pressure (BP), complete blood count, glucose and lipid analysis at admission. Patients: 65 patients were young adults (YA) and 309 were old (Od). Results: The CVD in YA represented 14% and in Od 66.7% of ali CVD admitted; male were more prevalent in YA (52.3%) and female in Od (58.3%). The most frequent type of CVD was ischemic (IS) (82.8% in YA and 82.1% in Od) with the lacunar sub-type more prevalent in YA (P-0.04) and the atherothrombotic in Od (P=0.004); TIA represen ted 8.3% of IS in YA and 3.3% in Od Previous stroke were reported in 20% YA and 32.7% Od (P=0.04). The dyslipidemia (43.1%), heavy alchool con sumption (24.6%) and cigarette smoking (12.3%) were more preval,ent in YA. There was heart disease in 36.9% YA and 52.4% Od (P=0.02); the valvular cardio-pathy was more prevalent in YA (18.5%). Infeccious complications were observed in 32.1% YA and 58.3% Od (P=0.001). The YA haved a good improvement (slight deficits in 56.8% YA vs 28.3% Od - P=0.001). The mortality rate in YA was 12.3% and in Od 30.4% (P=0.003). Conclusions: The preval,ence of CVD in YA was 14 %. We observed more prevalence of female in olders. The IS was the more frequent stroke in both groups, the lacunar sub-type was more frequent in YA and the atherothrombotic in Od The HT was the more frequent VRF in both groups. The valvular cardiopathy was more frequent in YA and atrial fibrillation in Od The morbility and mortality was higher in older patients. ln admission the mean level of dyastolic BP, total cholesterol, LDL-C and triglycerides were significantly higher in YA.